2013
DOI: 10.7763/ijcea.2013.v4.291
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ScCO2 Extraction of Rambutan Seed Oil Using Response Surface Methodology

Abstract: Abstract-Seed of rambutan as a waste of products from the canned fruit industry and was extracted by supercritical carbon dioxide (ScCO 2 ) using CO 2 as a solvent, maceration and soxhlet extraction using ethanol as the solvent. An optimization study of ScCO 2 extraction using response surface methodology was performed and 3D response surfaces were plotted from the mathematical models. The optimal conditions based on combination responses were: pressure (X 1 ) at 34.8 MPa, temperature (X 2 ) at 56.7 o C, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In contrast, increasing the extraction temperature at highest ethanol concentrations resulted to decreased, TF values. This phenomenon can be explained by the higher movement of the particles which causes plant tissue to rupture and hence allowing higher solubility of solvent until it starts to degrade to a lower value as it had achieved the stable state [ 26 ]. The results obtained for flavonoids are in agreement with the previous report from Cryptotaenia japonica hassk by Lu et al [ 27 ] where the flavonoid content increased when the temperature of extraction increased to below 70 °C and exhibited a decreasing trend above the optimum level of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, increasing the extraction temperature at highest ethanol concentrations resulted to decreased, TF values. This phenomenon can be explained by the higher movement of the particles which causes plant tissue to rupture and hence allowing higher solubility of solvent until it starts to degrade to a lower value as it had achieved the stable state [ 26 ]. The results obtained for flavonoids are in agreement with the previous report from Cryptotaenia japonica hassk by Lu et al [ 27 ] where the flavonoid content increased when the temperature of extraction increased to below 70 °C and exhibited a decreasing trend above the optimum level of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Surface methodology was a good tool for optimization of extraction conditions [17]. Table 2 presents the experimental design and corresponding response data for the extraction of the andrographolid.…”
Section: Resultsmentioning
confidence: 99%
“…Response Surface Methodology (RSM) is widely employed for constructing and exploring estimated functional relationship between a response variable and design variables [17]. The main advantage of RSM is the reduced number of experimental trials needed to evaluate multiple parameters and their interactions.…”
Section: Introductionmentioning
confidence: 99%
“…It is encouraging to compare Figure 3 with that found by Azahar et al (2017) whose found out that the flavonoid content increased as the temperature approached 70℃, and gradually decline as the temperature rise above its optimum temperature. A likely explanation is that higher temperature cause plant tissue rupture, thus solvent was easily to dissolved and degrade active compounds in the plant (Azahar et al, 2017;Yoswathana, 2013). It is apparent from Figure 3 that the best temperature for flavonoid extraction is 60˚C regardless of whether the seeds were treated or not prior to extraction.…”
Section: The Effect Of Extraction Temperature On Total Flavanoid Content (Tfc)mentioning
confidence: 99%